(untitled) (Global Journal of Management and Business Research, 2023)
Restate business is increasingly expanding and gradually meeting the diverse needs of customers with real estate needs This expansion also creates fierce competition in the market not only in terms of price but also in quality The real estate business environment has made great progress creating a transparent and clear legal environment thereby helping the real estate industry to make great strides Along with the development of the real estate industry more and more companies were established new types of real estate business appeared the Law on Real Estate Business began to have many limitations and inadequacies in the process Adjust the law on real estate business conditions Money laundering in real estate business should be prevented and prevented The article studies the real estate business of foreign investors in accordance with Vietnamese law and proposes recommendations to improve the law on real estate business of foreign investors in Vietnam